Investment decisions in a changing South Africa from 1990 to 1999 (transition) : analysis of the decade of the 1990s - Harris, Stanley E. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2003.